2016
DOI: 10.1016/j.acvd.2015.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Syncope unit in the paediatric population: A single-centre experience

Abstract: Syncope units in the paediatric population may be useful in the diagnostic process, to help identify rare cardiac aetiologies, and could decrease recurrence through specific management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…1,14,13 Patients with cardiac syncope had symptoms in the form of palpitation and chest pain. In the patient with complete heart block syncopal event was triggered after exercise There are many studies showing vasovagal syncope as the commonest cause of syncope, consistent with the present study that is Courtheix et al, Schuster et al, Day et al 5,15,16 These findings suggest that every patient who has even one syncopal attack should be promptly investigated since the underlying cause could be a benign one like a vasovagal syncope where symptomatic treatment can bring about sufficient improvement in symptoms.…”
Section: Discussionsupporting
confidence: 87%
“…1,14,13 Patients with cardiac syncope had symptoms in the form of palpitation and chest pain. In the patient with complete heart block syncopal event was triggered after exercise There are many studies showing vasovagal syncope as the commonest cause of syncope, consistent with the present study that is Courtheix et al, Schuster et al, Day et al 5,15,16 These findings suggest that every patient who has even one syncopal attack should be promptly investigated since the underlying cause could be a benign one like a vasovagal syncope where symptomatic treatment can bring about sufficient improvement in symptoms.…”
Section: Discussionsupporting
confidence: 87%
“…The syncope guidelines of ACC indicated that psychogenic accounted for 8%−15% of cases ( 12 , 15 ). However, Courtheix et al ( 16 ) described 5.1% of CS in children with syncope in a single center. This may be because the single-center study could not represent the incidence and spectrum of the underlying diseases of syncope.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a positive screen result (abnormal history, P/E, and ECG), echocardiogram is most likely normal in children with syncope [ 18 ]. Exercise-induced syncope is highly associated with cardiac origins, mainly with ECG abnormalities with susceptibility to arrhythmia but with normal echocardiography in most cases [ 19 ]. In this study, there was no effect of syncope in the percentage of abnormal Holter results.…”
Section: Discussionmentioning
confidence: 99%